Ferromagnetic dual topological insulator in a two-dimensional honeycomb lattice. Issue 9 (10th July 2020) - Wang, Hao; Mao, Ning; Niu, Chengwang; Shen, Shiying; Whangbo, Myung-Hwan; Huang, Baibiao; Dai, Ying
Abstract : Magnetic topological insulators (TIs), including the quantum anomalous Hall effect and antiferromagnetic TIs, have attracted significant attention owing to the exotic properties they give rise to, however, ferromagnetic TIs with gapless surface/edge states and a nonzero topological invariant have not been reported so far. Abstract : Magnetic topological insulators (TIs), including the quantum anomalous Hall effect and antiferromagnetic TIs, have attracted significant attention owing to the exotic properties they give rise to, however, ferromagnetic TIs with gapless surface/edge states and a nonzero topological invariant have not been reported so far. Here, we show that a ferromagnetic topological insulating phenomenon is possible in a single layer honeycomb lattice on the basis of perturbation theory and model Hamiltonian analyses. As a probable candidate for the experimental realization of this phenomenon, we propose a hypothetical single-layer Na2 MnPb with supporting evidence based on first-principles calculations. The topological nature of the single-layer Na2 MnPb is confirmed by calculating the Wannier charge center, the spin Chern number, and the gapless edge states.